INDEKS SENSITIFITAS STRES BEBERAPA VARIETAS PADI GOGO PADA CEKAMAN KEKERINGAN - Jeki, Jeki (AGROTEKBIS, 2016)
One of the important issues in the field of cultivation of agricultural crops is the impact of the global warming on plant growth and crop production. The global warming indirectly affects growth and production of one of them through the drought on agricultural lands. It is important to identify the impact of drought on upland rice plant growth by determining its stress sensitivity index. The research was conducted Bendosari of Madurejo village of Sleman, in the Laboratory of Plant Sciences and in the Cropping Management Laboratory of Faculty of Agriculture, Gadjah Mada University in January â May 2013. The difference between the Stress Sensitivity Index of Upland Rice Varieties tested in this study shows that the genetic differences between plants causing each plant has a different response to drought stress beginning with biochemical response and then have an impact on plant morphology.Â Key Words : Drought stress, paddy land, sensitifity stress indeks.